BENEFITS THAT ISLAMIC AND CONVENTIONAL BANKS CAN ATTAIN BY IMPLEMENTING GREEN BANKING - Kashfia Sharmeen; Ahsan Mahbub Yeaman (Journal of Islamic Monetary Economics and Finance, 2020)
This paper aims to ascertain the benefits that Islamic and conventional banks in Bangladesh can reap by implementing green banking, and also the drivers that motivate banks to behave environmentally. The Green Compliance Index (GCI) was introduced here to measure banks’ environmental behaviour. It was prepared based on central bank guidelines. In this study, with the participation of all 40 private commercial banks (PCBs), 32 conventional banks and 8 Islami Shariah-based PCBs, firm specific variables were collected through content analysis of the GCI. Structural equation modelling-partial least squares (SEM-PLS), together with the bootstrapping method, were used to evaluate the research data. These were collected and sorted from the FY annual report of 2018. For further support, a generalized linear model (GLM) was used to assess the outcomes. The results show that the effects of green compliance on possible benefits are significantly higher for Islamic banks. In contrast, these banks comply less with the green banking codes than conventional banks do in Bangladesh. Company size and the independence of bank directors appear to have a significant influence on compliance with the green banking codes, while governance does not show such an association for either group of banks. As Islamic banks have a greater scope to attain benefits, policymakers should introduce more interactive green banking products and loan schemes for prospective consumers, especially in industrial sectors where there is a greater possibility of being sustainable and environmentally friendly. Based on the findings, policy recommendations are made for practitioners, regulators and future researchers.